2017
DOI: 10.1080/10428194.2017.1339878
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targeting of inosine-5’-monophosphate dehydrogenase by FF-10501 promotes erythropoiesis via ROS/MAPK pathway

Abstract: One of the major symptoms of myelodysplastic syndromes (MDS) is severe cytopenia. Despite cytokine therapies, such as erythropoiesis-stimulating agents, many patients still require blood transfusions, and the development of new therapeutic approaches is needed. In this work, we studied the effects of the inosine-5'-monophosphate (IMP) dehydrogenase (IMPDH) inhibitor FF-10501 on erythropoiesis of human hematopoietic cells. Differentiation of K562 chronic myeloid leukemia cells to an erythroid lineage was promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previous studies in erythroleukemia have shown that both purine supplementation (29,30) and inhibition of purine synthesis (31,32) can induce erythroid differentiation. Therefore, the early inhibition of purine synthesis led us to hypothesize that perturbation of this pathway drives a stress response that results in erythroid cell differentiation.…”
Section: Purine Biosynthesis Inhibition Is An Early Event Following F...mentioning
confidence: 99%
“…Previous studies in erythroleukemia have shown that both purine supplementation (29,30) and inhibition of purine synthesis (31,32) can induce erythroid differentiation. Therefore, the early inhibition of purine synthesis led us to hypothesize that perturbation of this pathway drives a stress response that results in erythroid cell differentiation.…”
Section: Purine Biosynthesis Inhibition Is An Early Event Following F...mentioning
confidence: 99%
“…Previous studies in erythroleukemia have shown that both purine supplementation 19,20 and inhibition of purine synthesis 21,22 can induce erythroid differentiation. Therefore, the early inhibition of purine synthesis led us to hypothesize that perturbation of this pathway drives a stress response that results in erythroid cell differentiation.…”
Section: Purine Biosynthesis Inhibition Is An Early Event Following F...mentioning
confidence: 99%